Pengaruh Kecerdasan Spiritual terhadap Kinerja Karyawan melalui Organizational Citizenship Behavior pada PT PLN (Persero) Area Bojonegoro - HIDAYAH, ROMADHOTIN (Jurnal Ilmu Manajemen (JIM), 2018)
PT PLN (Persero) is a state-owned organization hold in electrical services, this company has a monopoly right to electricity sales in Indonesia and its existence is needed by the community. PT PLN requires to maintain the good employ`s performance in improvements and services to achieve the organizational goals in accordance with the vision and mission set. The objectives of this study are to examine and analyze the influence of spiritual intelligence on employ`s performance , the influence of organizational citizenship behavior on employ`s performance and the spiritual intelligence on employee performance through organizational citizenship behavior. In this study, the sample used is permanent employees of PT PLN (Persero) Area Bojonegoro which amounted to 63 people. The data analysis technique used is Structural Equation Model (SEM) with smartPLS 3 program. The results of this study indicate that spiritual intelligence has a significant positive effect on employ`s performance,the spiritual intelligence has a significant positive effect on organizational citizenship behavior.The organizational citizenship behavior also has a significant positive effect on employ`s performance .Beside that,the organizational citizenship behavior able to mediate the influence between spiritual intelligence on employ`s performance. Keywords : Spiritual Intelligence, organizational citizenship behavior, employ`s performance.